ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TARIF PAJAK EFEKTIF PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DIBURSA EFEK INDONESIA - , Tengku Eka Susilawaty (Universitas Pembangunan Panca Budi, 2020)
Effective Tax Rate is the ratio between tax expense and taxable income. ETR is very useful to measure how much the actual tax burden will be paid by the Taxpayer. This study aims to examine the effect of Firm Size, Profitability, Leverage, Capital Intensity, and Inventory Intensity towards Effective Tax Rates in Food and Beverage Companies that are listed in Indonesia Stock Exchange. The research approach used In this associative. The samples in this research is determined using Saturation Sampling Method where there are 13 companies that meets the criteria for the years of observation from 2014 to 2018. The data analysis technique used is descriptive statistic, multiple linear regression test of panel data model, hypothesis test (t-test and F-test) and test for coefficient of determination. The results of this study indicate that partial Firm Size, Leverage and Capital Intensity effect white the Effective Tax Rate, while Profitability and Inventory Intensity no effect the Effective Tax Rate. Then the Firm Size, Profitability, Leverage, Capital Intensity and Inventory Intensity simultaneously effect the Effective Tax Rate. Thus, the decision makers can use these ratio as a tool of consideration in making policies in the system of taxation on the company.